Ensino-aprendizagem de biologia vegetal através da construção de um guia ilustrado e de um blog sobre a flora nativa do parque estadual Sítio Fundão, Crato-CE - Costa, Edylla Maria Pereira (2024)
There are many challenges in teaching when it comes to plant biology. Students do not perceive plants o living beings, much less their importance in the environment, making the study of plants boring. This predisposition not to recognize plants and their importance is defined by many authors as "botanical imperception", and it is necessary to analyze and reflect on this issue. Therefore, rethinking new teaching strategies that bring students closer to their reality is essential for meaningful learning in biology. With a view to effective, relevant and active learning, which promotes student engagement and protagonism in the construction of scientific knowledge, inquiry-based teaching, by giving meaning to learning, provides favorable conditions. The aim of the research was to develop strategies for teaching botany that foster meaningful and contextualized learning in the ecosystem of the region where the study was carried out. The research was carried out at the EEMTI Governador Adauto Bezerra, located in the municipality of Crato, Ceará, and was aimed at 25 students in the second year of secondary school. Participant observation was used to conduct the research. A didactic sequence allowed them to learn a little more about the biome in which they live and encouraged the students to take an investigative stance, favoring the teaching of botany. The research showed that there are limitations related to students' knowledge of botany, but the proposal for investigative lessons generated interest and a more attractive relationship between teaching and learning, by encouraging students to seek knowledge in a pleasurable way, leading them to overcome limitations imposed by traditional teaching models.